First record of the oil-collecting bee Centris (Odontoxys) melanochlaena Smith, 1874 (Hymenoptera, Apidae) in Nicaragua - Quiroz-Medina, Conrado Ronaldo (2023)
The first report of the oil-collecting bee Centris (Odontoxys) melanochlaena Smith, 1874 in Nicaragua is presented. This species occurs in several Central American countries and Mexico, being this the first record from western Nicaragua. This record contributes to the knowledge of the distribution range of this species, as well as increases the list of native bees occurring in Nicaragua.